Manifestation of Self-Directed Learning by Adult Students in A Post-Graduate Distance Education Program - Daing Ibrahim, Daing Zaidah (2002)
The purpose of this research is to understand the manifestation of self-directed learning by a group of adult students studying in a post-graduate distance education program. The research is conducted by examining four research questions: (1) What characteristics of participants as learners are manifested that predispose them to be self-directed?; (2) What are the motivational factors that predispose learners to be self-directed?; (3) What are the self-directed learning activities carried out by learners in the distance education program?; and (4) what are the contextual factors that influence the manifestation of self-directed learning? The study employs the qualitative methodology and the data are collected through in-depth interviews with participants. Informal observations, examination of available documents and interviews with spouses and colleagues are carried out to verify information given by participants. The adult students were purposefully selected to participate in this study. They included seven adult students studying on a part-time basis in the Master of Science in Human Resource Development program, through distance education at a local university. Interviews have been conducted to obtain their perception, experiences, activities related to self-directed learning in a post-graduate distance education program. The main source of data is from the semi-structured interviews that were taped, transcribed and analyzed. The interviews with the participants lasted for one and a half to two hours. The study reveals seven characteristics as manifested by the adult students that predispose them to be self-directed, five motivational factors that explained their self-directedness, and two contextual factors that influence the manifestation of self-directed learning. Apart from these findings, one distinct aspect has emerged from the study. It was the transformation of adult students into lifelong self-directed learners as a result of the distance education process that they have gone through.